Oxytocin influences avoidant reactions to social threat in adults with borderline personality disorder. (16th August 2013) - Brüne, Martin; Ebert, Andreas; Kolb, Meike; Tas, Cumhur; Edel, Marc‐Andreas; Roser, Patrik
Abstract : Background: Borderline personality disorder (BPD) is characterized by interpersonal dysfunction, emotional instability, impulsivity, and risk‐taking behavior. Recent research has focused on the role of oxytocin in BPD, with mixed results as regards the processing of social stimuli. Methods: In a double‐blind randomized placebo‐controlled study, 13 BPD patients and 13 controls performed a dot probe task to examine attentional biases to happy and angry faces after intranasal application of oxytocin or placebo. Childhood trauma was examined using the childhood trauma questionnaire. Results: In the placebo condition, patients with BPD (but not controls) showed an avoidant reaction to angry faces (but not happy faces). The strength of the avoidant reaction correlated with the severity of childhood trauma. This behavioral response (as well as the correlation) was abolished in the oxytocin condition. Conclusions: Adult patients with BPD show an avoidant response to social threat, a reaction that is linked with traumatic experiences during childhood. This response pattern is altered by oxytocin, possibly by reducing stress and inhibiting social withdrawal from distressing social stimuli. Copyright © 2013 John Wiley & Sons, Ltd.